2009
DOI: 10.1024/0036-7281.151.6.287
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings in an alpaca with Mycobacterium kansasii infection

Abstract: This case report describes the clinical, ultrasonographic and postmortem findings in an alpaca with Mycobacterium kansasii infection. The alpaca was referred because of chronic weight loss and weakness. The results of clinical examination, haematology and serum biochemistry were not diagnostic. Ultrasonography of the liver revealed multiple, hyperechogenic lesions with a diameter of 1 to 3 cm. Histological evaluation of a liver biopsy sample showed acute, multifocal, suppurative, necrotising hepatitis. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…More recently, there has been a move towards more conservative surgical management in humans because M. ulcerans has a relatively predictable antibiogram. avium, 34 M. bovis, 35 M. microti 36,37 and M. kansasii; 38,39 however, no reports of treatment of these infections (from which treatment of M. ulcerans infection could be extrapolated) have been recorded. 33 A recent case series of dogs with M. ulcerans infection confirmed that the combination of rifampicin and a fluoroquinolone (with or without surgical debridement) was effective in curing the disease within 8-10 weeks in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, there has been a move towards more conservative surgical management in humans because M. ulcerans has a relatively predictable antibiogram. avium, 34 M. bovis, 35 M. microti 36,37 and M. kansasii; 38,39 however, no reports of treatment of these infections (from which treatment of M. ulcerans infection could be extrapolated) have been recorded. 33 A recent case series of dogs with M. ulcerans infection confirmed that the combination of rifampicin and a fluoroquinolone (with or without surgical debridement) was effective in curing the disease within 8-10 weeks in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (Johne's disease), 26 M. avium subsp. avium, 34 M. bovis, 35 M. microti 36,37 and M. kansasii; 38,39 however, no reports of treatment of these infections (from which treatment of M. ulcerans infection could be extrapolated) have been recorded. Likewise, there is a paucity of information about the treatment of mycobacterial infections in dromedaries.…”
Section: Southmentioning
confidence: 99%
“…A 1-year-old female domestic shorthair cat presented with anorexia, depression, and weight loss, accompanied by multifocal nodules affecting the face and occasional ulceration affecting the ears, periocular areas, and nasal planum [37]. Infection with obvious clinical signs and coinciding lymphadenitis or lung lesions have been reported in rhesus monkeys (Macaca mulatta), cattle (Bos taurus), llamas (Lama glama), alpacas (Vicugna pacos), goats (Capra hircus), camels (Camelus), and domestic pigs (Sus scrofa f. domestica) [33,38]. The extensiveness of the range of animal species susceptible to infection with MKC poses a high risk of uncontrolled transmission of the pathogen in the environment, as is often the case with M. bovis [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered an important pathogen causing pulmonary and cutaneous disease in people . Although there have been some reports in wild animals with disseminated M kansasii infection, there was only one report of a dog . This organism is usually not transmitted between individuals .…”
Section: Discussionmentioning
confidence: 99%